Response switching and self-efficacy in Peer Instruction classrooms - Kelly Miller (American Physical Society, 2015)
Peer Instruction, a well-known student-centered teaching method, engages students during class through structured, frequent questioning and is often facilitated by classroom response systems. The central feature of any Peer Instruction class is a conceptual question designed to help resolve student misconceptions about subject matter. We provide students two opportunities to answer each question—once after a round of individual reflection and then again after a discussion round with a peer. The second round provides students the choice to “switch” their original response to a different answer. The percentage of right answers typically increases after peer discussion: most students who answer incorrectly in the individual round switch to the correct answer after the peer discussion. However, for any given question there are also students who switch their initially right answer to a wrong answer and students who switch their initially wrong answer to a different wrong answer. In this study, we analyze response switching over one semester of an introductory electricity and magnetism course taught using Peer Instruction at Harvard University. Two key features emerge from our analysis: First, response switching correlates with academic self-efficacy. Students with low self-efficacy switch their responses more than students with high self-efficacy. Second, switching also correlates with the difficulty of the question; students switch to incorrect responses more often when the question is difficult. These findings indicate that instructors may need to provide greater support for difficult questions, such as supplying cues during lectures, increasing times for discussions, or ensuring effective pairing (such as having a student with one right answer in the pair). Additionally, the connection between response switching and self-efficacy motivates interventions to increase student self-efficacy at the beginning of the semester by helping students develop early mastery or to reduce stressful experiences (i.e., high-stakes testing) early in the semester, in the hope that this will improve student learning in Peer Instruction classrooms.